Clinical predictors of causative radiographic findings in adults with acute onset diplopia - Son, Yubin; Suh, Hie Bum; Choi, Hee-young; Cabrera, Michelle T.; Jeon, Hyeshin (Frontiers in Neurology, 2024)
ObjectiveThis study aimed to investigate the clinical factors that predict abnormal radiographic findings in adults with acute onset binocular diplopia.MethodsMedical records of consecutive patients aged >20 years who presented with acute binocular diplopia were retrospectively reviewed. Patients were divided into positive and negative groups according to radiographic findings. Demographic and clinical characteristics were compared. The risk factors for positive radiographic findings were investigated, and the area under the receiver operating characteristic curve (AUC) was calculated.ResultsAmong 242 patients (145 males and 97 females), 44 (18.2%) were in the positive group and 198 (81.8%) in the negative group. Patients in the positive group were older (p = 0.005) and had more vasculopathic risk factors (p = 0.038). Severe duction limitation (>50% reduction in motility) was present in 90.9% of patients in the positive group and 56.1% in the negative group (p < 0.001). Abnormal slit lamp findings and pupillary exam abnormalities were also more frequent in the positive group than in the negative group (p = 0.027 and p = 0.036, respectively). Older age, higher intraocular pressure, abnormal slit-lamp findings, exophthalmos, and duction limitation were identified as risk factors for positive radiographic findings. A predictive model generated an AUC of 0.772.ConclusionOlder age and vasculopathic risk factors were associated with underlying radiographic pathologies, supporting the recommendation that neuroimaging should not be delayed in those patients. Careful ophthalmic evaluations may guide diagnosis and decision-making for immediate neuroimaging in cases of diplopia.